2015
DOI: 10.1097/ccm.0000000000000691
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Vasopressor Support During Targeted Temperature Management at 33°C Versus 36°C After Out-of-Hospital Cardiac Arrest

Abstract: Targeted temperature management at 33 °C was associated with hemodynamic alterations with decreased heart rate, elevated levels of lactate, and need for increased vasopressor support compared with targeted temperature management at 36 °C. Low mean arterial pressure and need for high doses of vasopressors were associated with increased mortality independent of allocated targeted temperature management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
6
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 30 publications
2
107
6
4
Order By: Relevance
“…Ancak, 33°C'de hedefli sıcaklık yönetimi yapılan olgularda 36°C grubuna göre kalp hızı azalması, artan laktat düzeyleri, artan vazopressör destek ihtiyacı ve daha yüksek bir genişletilmiş kardiyovasküler SOFA skoru saptandığı bildirilmektedir (4,5). Bu durum ve kritik olan arrest sonrası bakım sürecinde 36°C'ye yaklaşan vücut sıcaklığının herhangi bir dezavantaja neden olmadığı göz önünde bulundurularak, Uluslararası İleri Yaşam Desteği Görev Grubu Resusitasyon Bağlantı Komitesi önerileri doğrultusunda Avrupa Resusitasyon Derneği (ERC) 2015 Kardiyopulmoner Resusitasyon Kılavuzunda değişiklik yapılmıştır (6):…”
Section: Sonuçunclassified
See 1 more Smart Citation
“…Ancak, 33°C'de hedefli sıcaklık yönetimi yapılan olgularda 36°C grubuna göre kalp hızı azalması, artan laktat düzeyleri, artan vazopressör destek ihtiyacı ve daha yüksek bir genişletilmiş kardiyovasküler SOFA skoru saptandığı bildirilmektedir (4,5). Bu durum ve kritik olan arrest sonrası bakım sürecinde 36°C'ye yaklaşan vücut sıcaklığının herhangi bir dezavantaja neden olmadığı göz önünde bulundurularak, Uluslararası İleri Yaşam Desteği Görev Grubu Resusitasyon Bağlantı Komitesi önerileri doğrultusunda Avrupa Resusitasyon Derneği (ERC) 2015 Kardiyopulmoner Resusitasyon Kılavuzunda değişiklik yapılmıştır (6):…”
Section: Sonuçunclassified
“…Serebral performans kategorisi (SPK) ve modifiye Rankin ölçeği (mRÖ) gibi ölçümler uzun dönemde sağkalanlar üzerinde nörolojik hasarın az ya da hiç olmadığını gösterse de daha detaylı nörofizyolojik araştırmalar azalan bir hayat kalitesi ve artmış bir bakım ihtiyacını ortaya koymaktadır (3)(4)(5).…”
Section: Introductionunclassified
“…En analyse post-hoc de l'ensemble de l'effectif de l'étude multicentrique TTM (n=950), on retrouvait dans le groupe 33°C (vs 36°C) une fréquence cardiaque moindre (-7 c/min soit -10 %) associée à une élévation du lactate (+0,6 mmol/L soit +30 %), mais une pression artérielle moyenne et une fraction d'éjection ventriculaire gauche à J1 similaires [54]. Un besoin accru en vasopresseurs, défini par un score SOFA cardiovasculaire à 4 (vs ≤ 3) dans les 36 premières heures de traitement, était plus fréquemment retrouvé dans le groupe 33°C vs 36°C (54 % vs 45 % respectivement).…”
Section: Choc Cardiogénique Et Hypothermieunclassified
“…A recent study showed inverse effect between arterial pressure and survival [53]. In the absence of definitive data, the ERC guidelines recommend a target blood pressure that secures a satisfactory urine output (1 ml/kg/h) and a decreasing/normalizing lactate level taking into consideration the patient's normal blood pressure [3].…”
Section: Cerebral Perfusionmentioning
confidence: 99%